DESCRIPTION OF THE CHARACTERISTICS OF THE EVENT OF MEASLES IN 2018-2019: A CASE STUDY AT SUKASADA COMMUNITY HEALTH CENTERS 1 - Putu Sukma Megaputri; Putu Dian Prima Kusuma Dewi (Rena Cipta Mandiri, 2022)
Measles is still a threat and cause of death and illness in infants, toddlers and children. Measles events still occur every year, even though they have already been immunized and treated with vitamin A. The goal of this study is to provide an overview of the characteristics of measles events in 2018-2019 in Puskesmas Sukasada 1. Descriptive research method to determine the epidemiological description of measles cases in 2018-2019 at Sukasada Health Center. This study uses secondary data from the measles event register in Sukasada. The data is then entered through to software analysis. The results showed that the incidence of measles occurred at an average age of 10 years with an average incubation period (fever to rash) of 1 day. Then most of these incidents were experienced by the gender of women who had been vaccinated and given vitamin A. The conclusion was that there were still many measles events, although they had immunization and administration of vitamin A in the past.